Nutrient concentration of two formulations of fermented fertilizers (biols) elaborated with local inputs - Rojas-Espinoza, Bruno Fabián; Hernández-Chontal, Mario Alejandro; Rodríguez-Orozco, Nereida; Linares-Gabriel, Ariadna (REVISTA TERRA LATINOAMERICANA, 2023)
In the current context of agroecological transition, the use of fermented fertilizers or biols has intensified. The objective of this study was to compare the nutrient concentration of two formulations of fermented fertilizers elaborated with local inputs. Handmade biodigesters were designed and sheep manure and Kikuyo grass (Pennisetum clandestinum) were used. Two formulations were generated: Biol 1 (20% kikuyo grass, 30% sheep manure and 50% water) and Biol 2 (50% sheep manure and 50% water), which were fermented for 100 days and there were three replicates of each formulation. In the biols the organic matter and the concentration of the macronutrients N, P and K, as well as the concentration of the micronutrients Fe, Cu, Mn and Zn were determined. Biol 1 had a higher concentration of organic matter, N and Fe (P ≤ 0.05). It is concluded that the nutrient concentration of the biol was improved when the grass was added in the fermentation process. The use of local, low-cost and easily accessible inputs can be an alternative to produce biols.